Beda Efektivitas Pengaruh Pemberian TENS Dan Stretching Dengan Lllt Dan Stretching Terhadap Penurunan Nyeri Pada Kasus Sindroma Piriformis - Sri Suwarni; Fendy Nugroho (Poltekkes Kemenkes Surakarta, 2019)
Background: Piriformis syndrome causes a decrease in mobility thereby reducing productivity. Objective to find out the difference between giving TENS therapy with stretching and LLLT with stretching to reduce the comfort of cases of Piriformis syndrome. Subjects were 30 piriformis syndrome patients Methods:. Experimental with two pre and post test designs. ANALYSIS: normality test with saphiro wilk obtained VAS score data with normal distribution with p > 0.05 for the first group and LLLT postal group with abnormal distribution data p < 0.05, parametric test with paired sample test in group I get the results sought with significance value p = 0,000 and non parametric Wilcoxon test for group II with p = 0.001. Post and post different tests of the two groups with the mann whitney test obtained p = 0.028. Result: providing TENS therapy with stretching and LLLT with stretching respectively in reducing pain in the case of Piriformis syndrome. Conclusion: Provision of TENS therapy with stretching is more effective than LLLT with stretching in the sense of decreased in cases of Piriformis syndrome.